The Problem of Models and Modeling: One Teacher's Solution - Aviva B Dorfman (Networks: An Online Journal for Teacher Research, 2008)
Teaching and learning as complex, interactive, co-constructed processes (Bransford, Brown, & Cocking, 2000) make being a teacher a complicated task. Teachers’ problems are often ill-structured, options for possible solutions are many, and the criteria for consideration of different solutions do not necessarily indicate a right or wrong answer. According to Richardson (2003), because constructivism is a theory of learning and not a theory of teaching, the literature on constructivist pedagogy is sparse about what constitutes effective constructivist teaching. The story of how I solved my own long-standing teaching dilemma about modeling contributes to the articulation of elements of effective constructivist teaching.